The Malay version of the brief questionnaire on smoking urge: Translation and psychometric properties of the questionnaire - Ali Qais Blebil; Syed Azhar Syed Sulaiman; Mohamed Azmi Hassali; Juman Abdulelah Dujaili; Alfian Mohamed Zin (Springer, 2019)
This study aimed to evaluate the psychometric properties of Malay translated version of the brief questionnaire of smoking urges (QSU-Brief). The translation procedure was done following the standard guidelines. The reliability and validity of the Malaysian version scale were evaluated based on the data collected from 133 Malaysian smokers. The internal consistency was calculated to assess the reliability. Factor analysis and construct validity were performed to validate psychometric properties of the scale. Total Cronbach's alpha of the scale was 0.806. The exploratory factor analysis revealed two factors that accounted for 66.15% of the explained total variance. The first component consisted of items 1, 3, 6, 7, and 10, while the second component included the rest. The QSU-Brief total score had a significant positive relationship with exhaled CO level (r = 0.24; P = 0.005), number of cigarettes smoked per day (r = 0.30; P < 0.001) and other clinical factors. Items 2 and 5 loaded strongly on factor 2, whereas both items loaded ambivalently on two factors in the previous studies. This discrepancy might be clarified by language differences. The Malaysian QSU-Brief is a good candidate for evaluating urge to smoke in both clinical practice and clinical trials.